Investigation of Pathogenic Mechanism of Covert Mortality Nodavirus Infection in Penaeus vannamei - Liu, Shuang; Xia, Jitao; Tian, Yuan; Yao, Liang; Xu, Tingting; Li, Xupeng; Li, Xiaoping; Wang, Wei; Kong, Jie; Zhang, Qingli (Frontiers in Microbiology, 2022)
Viral covert mortality disease (VCMD), namely running mortality syndrome (RMS), was caused by emerging covert mortality nodavirus (CMNV), and had impacted shrimp farming in the past years in Asia and Latin America. The possible pathogenic mechanism of CMNV infecting Penaeus vannamei had been investigated in this study. In the natural infected disease shrimp individuals, histopathological and in situ hybridization (ISH) analysis verified that severe cellar structural damage and CMNV infection occurred in almost all cells composing the ommatidiums; vacuolation and necrosis, together with numerous CMNV-like particles could be observed in cytoplasm of most cell types of the ommatidiums under transmission electron microscopic (TEM). The challenge test results showed that a low CMNV starting infecting dose could cause the cumulative mortality of 66.7% ± 6.7% and 33.3% ± 3.6% of shrimp in the 31 day's outdoor and indoor farming trials, respectively. The shrimp individuals from the infection group grew slower than those from the control group; and the ratio of soft-shell individuals in the infection group (42.9%) was much higher than that of control group (17.1%). The histopathological and ISH examinations of individuals artificially infected with CMNV revealed that severe cellar damages including vacuolation, karyopyknosis, and structural failure occurred not only in the cells of the refraction part of the ommatidiums, but also in cells of the nerve enrichment and hormone secretion zones. And the pathological damages were more severe in the nerve cells both of the abdominal segment nerve cord and segmental nerve of the pleopods. TEM examination revealed the ultrastructural pathological changes and vast amount of CMNV-like particles in the abovementioned tissues. The differential transcriptome analysis showed that the CMNV infection resulted in the significant down-regulated expression of genes of photo-transduction, digestion, absorption and growth hormones, which might be the reason for slow growth of shrimp individuals infected by CMNV. This study uncovered the unique characteristic of neurotropism of CMNV for the first time, and explored the pathogenesis of slow growth and shell softening of P. vannamei caused by CMNV infection.